Determination of ‘tooth’ perception as the first step in development of oral health in Turkish society: A metaphor study (Annals of Medical Research, 2021)
Aim: This study aims to reveal the ‘tooth’ perceptions in the subconscious of individuals through metaphors.Material and Methods: The sample of descriptive study consisted of 302 adult individuals who resided in in Turkey. The data were collected by a semi-structured questionnaire form. The questionnaire was on the sociodemographic information of the participants, while the second part was on their tooth perceptions. It was asked to the participants for determining their tooth perceptions, it was aimed for them to produce a metaphor for their tooth perceptions and explain the reason for producing that metaphor.Results: At the study, it was observed that 66 different metaphors were produced. The metaphors that were produced were categorized under 3 themes concerning the function, aesthetic and overall characteristics of a tooth based on the things that teeth do. It was found that the tooth perceptions in the society were affected by age, gender, status of brushing, frequency of brushing and the population an individual is in, while these were not affected by income, smoking status and dental concerns. Aesthetical perceptions increased among young people, women and people with higher educational levels. The functional characteristics of teeth were more prioritized among people of more advanced ages, men and with lower educational levels (p0.05). Conclusion: With this metaphor study, it was understood that perceptions on teeth were mostly focused on aesthetical and/or functional elements, but there was an insufficient amount of perceptions that focused on teeth as organs with overall characteristics.
Keywords: Tooth perception; metaphor; oral health; dental esthetic; dental function.